Leaf epidermal anatomy of Cynodon dactylon (L.) Pers. in relation to ecotypic adaptation (Bangladesh Journal of Plant Taxonomy, 2021)
Qualitative and quantitative studies were done on leaf epidermal characteristics with special reference to stomatal features to find out the impact of environmental condition on twenty four accessions of Cynodon dactylon (L.) Pers. collected from different ecological habitats of Bangladesh. The foliar epidermal peels from both surfaces of mature leaves were observed under microscope. The leaves were found to be amphistomatic and stomata were paracytic type. The epidermal cells in this study were found to be sinuous. Silica bodies were found to be saddle and cross shaped. Prickles angular were pointed at the tip. Macro-hairs were present in all the accessions, but no micro-hair was found both adaxially or abaxially. Stomatal frequency and stomatal index were found to vary from accession to accession on both adaxial and abaxial surface of leaves, and the differences were statistically significant in most of the cases.Bangladesh J. Plant Taxon. 28(1): 171-193, 2021 (June)